As potencialidades das metodologias ativas para promover educação financeira com alunos nos anos finais da educação básica - Sousa, Pedro Henrique Oliveira (2024)
This work focuses on analyzing the contributions of active methodologies as an enhancer of financial education concepts for the training of students in the final years of Elementary School. Active methodologies are present in this work as an intervention strategy in which we seek for the student to develop autonomy and be responsible for building their knowledge. The development of financial education is one of the current themes and which makes up the National Common Curricular Base (BNCC), in this context, according to the Ministry of Education (MEC) portal, financial education is defined as the process through which “individuals and societies improve their understanding of financial concepts and products, so that, with information, training and guidance, they can develop the values and skills necessary to become more aware of the opportunities and risks involved”. Throughout the development of this work, I adopted as a methodological proposal to work on financial mathematical concepts and content based on activities based on active methodologies (peer instruction and flipped classroom). These methodologies would serve as a basis for the problematizations made around financial mathematics content, so that students are able to overcome the mechanical methods/techniques of memorizing content in favor of a better understanding and meaning of the content and their own learning.